Evaluating the Effects of Gamification in Behavioural Change: A Proposed SEM-Based Approach - Ourdas, Christos; Ponis, Stavros (Sustainability, 2023)
The purpose of this study is two-fold. Firstly, it aims to investigate the available papers on the effect of gamification elements to explain behavioural changes through a Systematic Literature Review (SLR). Secondly, based on the SLR, it proposes a four-step SEM (Structural Equation Model)-based approach that can be used to validate the effects of gamification on behavioural change and can be further applied in the context of a research project that aims to lower maritime plastic pollution in coastal areas. The SLR approach provides an overview of empirical studies that successfully measure the three identified objectives, i.e., increased (O1) usage of a web platform, (O2) awareness, and (O3) participation in behaviour, and it focuses on SEM to collect empirical results. Findings from the SLR highlight multiple research shortcomings, such as the lack of a unified taxonomy for gamification and motivational affordances, the absence of studies soundly linking gamification elements to psychological outcomes, and the tendency of researchers to measure the intention to conduct a behaviour rather than the long-term effect of actual behaviour changes. Finally, the created approach provides insights on which gamification elements to include and how to measure their behavioural effect based on a self-developed SEM and questionnaire, which can be applied in research projects utilising gamification, independent from the domain of activity.
CRIS-Team WoS Importer:2023-04-21